Best practices for IBM DS8880 and IBM z/OS HyperSwap with IBM Copy Services Manager - Luther, Thomas; Warmuth, Alexander; Takakura, Marcelo (IBM redbooks., 2019)
Many IBM® z/OS® customers require their applications to be available 24x7. Whether the business requirements are high availability (HA), disaster recovery (DR), or business continuity, IBM HyperSwap® technology can provide an adequate solution. HyperSwap is the industry standard and is provided as several different implementation options to meet the various business needs of the IBM System z® and z/OS customer base. IBM Copy Services Manager (CSM) enables you to manage z/OS HyperSwap and helps you manage planned and unplanned actions in an z/OS environment from an open systems environment. This IBM Redbooks® publication provides best practices for the planning, implementing, integrating, and managing z/OS HyperSwap with CSM.